Effectiveness of New Therapeutic Techniques in Addressing Anxiety Disorders in a Clinical Setting - Utama, Atika Widya; Vann, Dara; Sothy, Chak (Yayasan Adra Karima Hubbi, 2025)
Anxiety disorders are among the most prevalent mental health conditions worldwide, significantly impacting individuals’ quality of life and daily functioning. Traditional therapeutic techniques have shown varying degrees of effectiveness, necessitating the exploration of innovative approaches to enhance treatment outcomes. This study investigates the effectiveness of new therapeutic techniques in addressing anxiety disorders within a clinical setting. The research aims to evaluate the impact of these techniques, which integrate cognitive-behavioral therapy (CBT) with exposure therapy and mindfulness-based interventions. A mixed-methods design was employed, combining quantitative and qualitative approaches. The study involved 150 participants diagnosed with anxiety disorders, randomly assigned to either an intervention group or a control group receiving standard treatment. Data were collected through standardized anxiety scales, semi-structured interviews, and behavioral assessments. The results indicate significant reductions in anxiety symptoms among the intervention group compared to the control group (p < 0.01). Participants reported improved emotional regulation, reduced avoidance behaviors, and enhanced overall well-being. Qualitative findings supported these outcomes, highlighting increased self-awareness and resilience among participants. The study concludes that the integration of new therapeutic techniques is effective in treating anxiety disorders, providing a viable alternative to conventional methods.